Cooperative Learning Model Type Make A Match in Social Studies Lessons to Increase Learning Activity of Elementary School Students - Trimansyah Trimansyah (FASHLUNA, 2026)
This study aims to see and examine the extent to which student learning activity has increased by implementing the make a match type cooperative learning model . Because to increase student learning activity, teachers need to be creative in providing fun lessons, especially preparing innovative models, so that students can understand the material well, especially social studies material that discusses natural phenomena and the social environment that exists around students' lives. For example, the make a match type cooperative learning model . The results of the study show that the use of this model is able to increase student activity, this can be seen from the active presentation of students from 35% increasing to 88%, this shows a significant increase from the previous learning process. In addition, this model can make learning more interesting, fun, more lively, and meaningful, because it is marked by students' attitudes in receiving learning much more enthusiastically than before, they have dared to ask, answer, discuss, more than that physically involved and actively participating in learning such as looking for pairs of cards that have been prepared by the teacher without shame and fear. So the make a match type cooperative learning model is very good to be applied in elementary schools.